2021
DOI: 10.1186/s13071-021-04690-w
|View full text |Cite
|
Sign up to set email alerts
|

Roles of three putative salmon louse (Lepeophtheirus salmonis) prostaglandin E2 synthases in physiology and host–parasite interactions

Abstract: Background The salmon louse (Lepeophtheirus salmonis) is a parasite of salmonid fish. Atlantic salmon (Salmo salar) exhibit only a limited and ineffective immune response when infested with this parasite. Prostaglandins (PGs) have many biological functions in both invertebrates and vertebrates, one of which is the regulation of immune responses. This has led to the suggestion that prostaglandin E2 (PGE2) is important in the salmon louse host–parasite interaction, although studies of a salmon lo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
9
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8
1

Relationship

4
5

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 88 publications
(61 reference statements)
2
9
0
Order By: Relevance
“…It is also unlikely that such enzymes are deposited on the host skin during infestation given the low severity of lice induced lesions 6 , 7 , 23 , 25 . Furthermore, it has not been possible to experimentally confirm that lice derived PGE 2 is in fact taking part in the host-parasite interaction 59 , 60 , emphasizing that more studies like this, directly addressing the regulation and mode of action of glandular proteins, are needed to analyse the interaction taking place at the site of infestation. New knowledge on this topic may represent a promising fundament for the development of new immune based anti-salmon louse treatments.…”
Section: Discussionmentioning
confidence: 99%
“…It is also unlikely that such enzymes are deposited on the host skin during infestation given the low severity of lice induced lesions 6 , 7 , 23 , 25 . Furthermore, it has not been possible to experimentally confirm that lice derived PGE 2 is in fact taking part in the host-parasite interaction 59 , 60 , emphasizing that more studies like this, directly addressing the regulation and mode of action of glandular proteins, are needed to analyse the interaction taking place at the site of infestation. New knowledge on this topic may represent a promising fundament for the development of new immune based anti-salmon louse treatments.…”
Section: Discussionmentioning
confidence: 99%
“…It has also been suggested that the immunosuppressive effect of the parasite increase with parasite intensity (Holm et al, 2015). However, the mechanism behind salmon lice immunosuppression is not elucidated (Dalvin, Eichner, Dondrup, & Øvergård, 2021; Eichner, Øvergård, Nilsen, & Dalvin, 2015; Øvergård et al, 2016). A parasite intensity‐dependent host immune response in the skin is not supported by our findings here.…”
Section: Discussionmentioning
confidence: 99%
“…The immune response of Atlantic salmon against salmon lice is weak and delayed compared to other salmonids resulting in low levels of resistance to infestations (Braden et al., 2020). The inefficient immune response against lice, could in parts be due to the immunomodulatory capabilities of the parasite (Braden et al., 2020; Fast et al., 2007; Øvergård et al., 2016, 2018), but the mechanism is currently not known (Dalvin et al., 2021; Eichner et al., 2015). However, the lack of an efficient immune response towards the ectoparasitic lice may also result from selection for tolerance rather than resistance in Atlantic salmon.…”
Section: Discussionmentioning
confidence: 99%